Political Connections and Thin Capitalization on Tax Avoidance During The Covid-19 Pandemic - Istiqfarosita, Melinia; Abdani, Fadlil (E-Jurnal Akuntansi, 2022)
Taxes are Indonesia's primary source of revenue and play a major role in promoting economic progress. The Covid-19 epidemic is thought to be capable of motivating tax avoidance. Political connections and thin capitalization tend to be associated with tax avoidance practices. The purpose of this study is to measure the effect of political connections and thin capitalization on tax evasion. The sample used is a company registered on IDX 80 in 2020 and obtained as many as 48 companies using the purposive sampling technique as sampling technique. Multiple linear regression analysis was used in this study as an analytical technique using SPSS statistical software. According to the findings of this study, variabel in political connection have a significant impact on tax avoidance, whereas thin capitalization has a negative and insignificant impact.  Keywords: Tax Avoidance; Political Connection; Thin Capitalization.